Enhancing oil recovery by polymeric flooding with purple yam and cassava nanoparticles - Al-Jaber, Hasanain A.; Arsad, Agus; Tahir, Muhammad; Nuhma, Mustafa Jawad; Bandyopadhyay, Sulalit; Abdulmunem, Abdulmunem R.; Abdul Rahman, Anis Farhana; Harun, Zakiah; Agi, Augustine (MDPI - Open Access Publishing, 2023)
Significant amounts of oil remain in the reservoir after primary and secondary operations, and to recover the remaining oil, enhanced oil recovery (EOR) can be applied as one of the feasible options remaining nowadays. In this study, new nano-polymeric materials have been prepared from purple yam and cassava starches. The yield of purple yam nanoparticles (PYNPs) was 85%, and that of cassava nanoparticles (CSNPs) was 90.53%. Synthesized materials were characterized through particle size distribution (PSA), Zeta potential distribution, Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and transmission electron microscopy (TEM). The performance of PYNPs in recovering oil was better than CSNPs, as found from the recovery experiments. Zeta potential distribution results confirmed the stability of PYNPs over CSNPs (−36.3 mV for PYNPs and −10.7 mV for CSNPs). The optimum concentration for these nanoparticles has been found from interfacial tension measurements and rheological properties, and it was 0.60 wt.% for PYNPs and 0.80 wt.% for CSNPs. A more incremental recovery (33.46%) was achieved for the polymer that contained PYNPs in comparison to the other nano-polymer (31.3%). This paves the way for a new technology for polymer flooding that may replace the conventional method, which depends on partially hydrolyzed polyacrylamide (HPAM).